Variabilidade da comunidade zooplanctônica : testando a relação diversidade estabilidade e identificando os efeitos de distúrbios hidrológicos (secas) sobre a estabilidade da comunidade. - Simões, Nadson Ressyé (2010)
Temporal variability of communities is a natural property of ecological systems, which is influenced by the difference among environments and also by anthropogenic activities. Many studies have suggested that diversity can buffer this variability. This prompted the hypothesis that diversity produces stability. However, the stabilizing effect of diversity on ecosystem properties has been challenged. Studying two sets of lakes (with or without connectivity to the rivers) in the floodplain, we tested the hypothesis that the diversity-stability relationship depends on the environmental variability, which leads to a difference in the pattern of dynamic responses of species (synchrony and asynchrony). Moreover, it was also observed as disturbances produced by changes in hydrological regime affected the temporal variability of zooplankton community. In lakes with lower environmental variability (ponds connected), the variability of community was positively associated with diversity. However, in lakes with greater environmental variability, it was observed decrease in community variability with diversity. Environments without connectivity tend to have higher environmental variability, and therefore may produce different responses of species (asynchronous dynamics) and a consequent decrease in total variability of community, producing a positive relationship between diversity and stability. Computer simulations confirmed these results showing that, when asynchronous responses prevail over synchronous responses, the covariation tends to decrease becoming negative, decreasing the total community variability with increasing species richness, indicating that the diversity increases temporal stability community. It was also registered that the absence of floods changed the variability of zooplankton in connected lakes, increasing the temporal dissimilarity of community structure. This suggests that in the flood plains, flooding is the system component that aids in the maintenance of ecological processes and high biodiversity of these environments.